A review of online business regulatory framework to reduce IFF in Bangladesh - Sony, M M ABDULLAH AL MAMUN (Essays of Faculty of Law University of Pécs, Yearbook of [year], 2023)
Illicit Financial Flow (IFF) is a key development challenge all over the world. In developing countries, though IFF may take place in different ways, but over the past couple of years IFF via the digital ecosystem has been demanding a rethink of the existing legal structure. For instance, in Bangladesh, the fastest developing country, by today about five leading ecommerce companies have been accused of fraud mostly in supply chain management and also accused of money laundering issues. Therefore, the Bangladesh government has adopted Digital Commerce Guidelines. Since these e-commerce scams take place frequently, this raises the question of the effectiveness of this existing legal structure in Bangladesh and how the same legal framework can meet the challenge of IFF via digital platform. With the help of the comparative method, the research has tried to address these gaps in academic literature from a qualitative approach. This study has indicated that a flaw in Bangladesh's present regulatory system is the lack of legislative directions on how to supervise excessive discounts or predatory pricing. Finally, no cross-border e-commerce rules or recommendations have been established under the present legal regulatory framework. As a result, it is suggested that these flaws in the current policy be reconsidered to reduce IFF. Overall, the findings of this study will assist policymakers in defining additional actions aimed at reforming a robust digital regulatory environment.